Effect of Submucosal Injection of Tramadol on Postoperative Complications after Third Molar Surgery - Rehmat Feroz, Khursheed Ahmed, Syed Aijaz Ali Zaidi, Suneel Kumar Punjabi, Naheed Najmi, Syed Ghazanfar Hassan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the effectiveness of submucosal application of tramadol for acute postoperative pain, swelling and trismus. Material and Methods: A total of 84 patients having age between 18 to 35 years with irrespective of gender and require impacted mandibular 3rd molar extractions were included in study whereas patients with pericoronitis, periapical infection or lesions with respect to impacted 3rd molars, opposing traumatic occlusion or impinging upper 3rd molars or pregnant and lactating women were excluded in study. Subjects were distributed in two groups by port (chit) method i.e., Group A (Tramadol Group) with 42 patients and group B (sterile normal saline group) with 42 patients. Postoperative pain, swelling and trismus were recorded on Day 1, 2, 3 and 7 Results: Male patients were 25 (59.5%) and 25 (59.5%) and female patients were17 (40.5%) and 17 (40.5%) with mean age of25.7±4.7 (18-35) years and 26.5±4.9 (18-35) years in group A (Tramadol Group) and group B (Sterile Normal Saline Group) respectively. Post-operative findings in both groups were significantly different, group A (Tramadol Group) is better from group B (Sterile Normal Saline Group) in terms of post-operative pain, swelling and trismus. Conclusion: Submucosal Tramadol is more effective, safe and reliable than sterile normal saline in patients after third molar surgery.